Resolvin E3 ameliorates high‐fat diet‐induced insulin resistance via the phosphatidylinositol‐3‐kinase/Akt signaling pathway in adipocytes. Issue 3 (7th February 2022) - Shimizu, Tomohiko; Saito, Tsugumichi; Aoki‐Saito, Haruka; Okada, Shuichi; Ikeda, Hiroyuki; Nakakura, Takashi; Fukuda, Hayato; Arai, Syota; Fujiwara, Kouichi; Nakajima, Yasuyo; Horiguchi, Kazuhiro; Yamada, Sayaka; et al.
Abstract: Obesity‐associated type 2 diabetes mellitus is associated with the development of insulin resistance. Among several metabolites, resolvins that are metabolites of eicosapentaenoic acid have been shown to exert insulin‐sensitizing effects; however, the role of resolvin E3 (RvE3) in glucose metabolism has not been studied. In this study, the effect of RvE3 on glucose metabolism in mice with high‐fat diet‐induced obesity and 3T3L1 adipocytes was studied. C57BL/6 mice fed a high‐fat diet were administered RvE3, for which insulin tolerance, oral glucose tolerance tests, and the homeostasis model assessment of insulin resistance, were performed. RvE3 treatment significantly improved insulin sensitivity and glucose tolerance and regulated protein kinase B (Akt) phosphorylation in the adipose tissue. Moreover, RvE3 treatment enhanced the insulin‐stimulated glucose transporter 4 (Glut4) translocation, glucose uptake, phosphatidylinositol‐3‐kinase (PI3K) activity, and Akt phosphorylation in 3T3L1 adipocytes, whereas a PI3K inhibitor inhibited the enhanced insulin‐stimulated glucose uptake induced by RvE3. These findings indicate that RvE3 likely improves insulin sensitivity, resulting in the upregulation of glucose uptake in adipocytes by activating the PI3K/Akt signaling pathways. Collectively, the findings of this study show that RvE3 may play a role in glucose homeostasis and could be used as a potential therapeutic target for developing treatments for obesity‐associated diabetes.